PENDEKATAN DISCOVERY LEARNING DALAM PEMBELAJARAN PPKN: UPAYA MENUMBUHKAN SIKAP REFLEKSI DAN KESADARAN SOSIAL PADA PESERTA DIDIK SD - Leonardus Hare Ladjar; Bonevantura Magi Mudamakin; Claudia Aurelia Albertini Lona; Perpetua Felisitas Gesu; Fadil Mas’ud; Rahyudi Dwiputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Civic Education at the elementary school level plays a crucial role in fostering character development, social awareness, and reflective thinking among students. However, classroom practices still show that many students remain passive, have difficulty identifying simple social issues, and are not accustomed to expressing their opinions based on logical reasoning. Limited exploratory activities and the lack of opportunities to connect Civic Education concepts with real-life experiences hinder the achievement of learning objectives. This study aims to describe the implementation of the Discovery Learning model in Civic Education and analyze its influence on the development of students’ reflective attitudes and social awareness. This research employed a descriptive qualitative approach. Data were collected through classroom observations, interviews with the homeroom teacher, and documentation such as lesson plans, student worksheets, and reflective journals. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, supported by source and method triangulation to ensure the credibility of the findings. The results indicate that the Discovery Learning model enhances students’ active participation, thinking skills, and the quality of their arguments. Students were able to identify social problems, gather supporting evidence, express opinions logically, and connect real-life experiences with Civic Education values. Moreover, the model fostered improvements in empathy, cooperation, and social responsibility through collaborative tasks and structured reflective activities. Challenges encountered include limited instructional time, teacher readiness, and insufficient learning media. Overall, Discovery Learning is proven effective in promoting reflective thinking and strengthening students’ social awareness in elementary Civic Education.